Stephen Gilman, Del Arcipreste de Hita a Pedro Salinas. Universidad, Salamanca, 2002; 376 pp. - Sol Mora, Pablo (Nueva Revista de Filología Hispánica (NRFH), 2004)
Se reseñó el libro: Del Arcipreste de Hita a Pedro Salinas.